Comparative Analysis Between Lateral Orbital Rim Preservation and Osteotomy for Transorbital Endoscopic Approaches to the Cavernous Sinus: An Anatomic Study. Issue 1 (26th April 2018) - Noiphithak, Raywat; Yanez-Siller, Juan C; Revuelta Barbero, Juan Manuel; Otto, Bradley A; Carrau, Ricardo L; Prevedello, Daniel M
Abstract: BACKGROUND: Transorbital endoscopic approach (TOEA) to the cavernous sinus (CS) is a novel surgical technique. However, the necessity of lateral orbital rim (LOR) osteotomy is questionable. OBJECTIVE: To illustrate the surgical dissection of TOEAs to CS and to investigate the additional benefit of LOR osteotomy. METHODS: Anatomic dissections were carried out in 7 cadaveric heads (14 sides). The TOEAs were performed before and after LOR osteotomy; herein referred as the lateral transorbital approach (LTOA) and the lateral orbital wall approach (LOWA), respectively. The stereotactic measurements of the area of exposure, surgical freedom, and angles of attack around CS were quantified. RESULTS: LOWA increased larger area of exposure than LTOA at entry site (5.3 ± 0.6 cm 2 and 2.6 ± 0.6 cm 2, respectively; P < .001) but both of these techniques provided similar area of exposure at the surgical target site. With regard to the surgical freedoms, those afforded by LOWA were all significantly superior at all of the surgical targets with the difference ranged from 106.6% to 172.5%. No significant differences were found between the vertical angles produced by either approach. On the other hand, the horizontal angles achieved by LOWA were significantly more favorable. CONCLUSION: The TOEAs, either with or without LOR osteotomy are feasible for CS exposure. Although the incremental effect of maneuverability is attained following the LOR osteotomy, it should be performed selectively. Additional research is needed to further validate the safety and efficacy, as well as for precisely defining the clinical application of these techniques.